Comparative efficacy of eight traditional Chinese medicines combined with statins in the treatment of hyperlipidemia: a Bayesian network meta-analysis - Jiang, Ling; Fan, Wen; Zhou, Fangyu; Liu, Lihan; Pan, Maoxing; Yang, Qinhe; Zhang, Yupei (Frontiers in Pharmacology, 2025)
BackgroundHyperlipidemia drives global cardiovascular mortality by elevating risks of atherosclerosis and stroke. While statins are foundational, traditional Chinese medicines (TCMs) are widely combined with statins to boost efficacy. However, diverse TCM formulations lack comparative evidence in combination regimens, necessitating urgent evidence-based optimization.MethodsBased on preliminary literature review and component usage frequency analysis, 8 TCMs were included firstly. Then, we conducted a systematic search for RCTs that assessed 8 TCMs with traditional statin drugs (TT) for the treatment of hyperlipidemia. The search was conducted through September 30, 2024, and encompassed China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Database (CBM), Database of Chinese Sci-Tech Periodicals (VIP), Wanfang Database, PubMed, Web of Science, and Cochrane Library. Outcomes included clinical total effective rate, total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C). Risk of bias in RCTs was evaluated using Cochrane’s bias risk tool. Evidence synthesis was performed utilizing both direct and Bayesian network meta-analyses (NMA). Meta-regression analysis, subgroup analysis, publication bias analysis, and sensitivity analysis were employed to evaluate heterogeneity sources and efficacy robustness. Ranking analysis was implemented to comparatively assess clinical efficacy among eight TCMs. Evidence quality for each outcome was assessed using Grading of Recommendations, Assessment, Development, and Evaluation approach (GRADE). Overall, the proposed structured framework integrated high-frequency TCM screening, NMA-driven efficacy ranking, methodological validation, and mechanistic investigation to holistically evaluate therapeutic interventions for the first time.Results67 RCTs involving 7327 individuals and 8 TCMs were encompassed. Related analyses indicated TT + TCMs were more efficacious than TT monotherapy. Among 8 TCMs + TT, TT combined with Jiangzhi Tongmai Capsule (TT + JZTM) demonstrated the highest clinical total effective rate, TT combined with Dantian Jiangzhi Pill (TT + DTJZ) was the most effective in reducing TC, TT combined with Pushen Capsule (TT + PS) was the most effective in reducing TG, and TT combined with Jiangzhiling Tablet (TT + JZL) was the most effective in increasing HDL-C and reducing LDL-C.ConclusionNMA revealed the overall clinical efficacy of TT + JZL, TT + DTJZ, and TT + JZTM were ranked at the forefront in treating hyperlipidemia. These findings provide evidence-based guidance for tailoring TCM-statin combinations to target individualized lipid profiles.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024603979, identifier [CRD42024603979].